Sosialisasi tentang Pencegahan DBD dengan Pemanfaatan Biji Pepaya sebagai Larvasida untuk Mengatasi Perkembangan Nyamuk di SMK Duta Karya - Aprillia Puspitasari Tunggadewi; Luvita Gabriel Zulkarya; Luthfiana Nurulin Nafi’ah; Yanulia Handayani; Wildayanti Wildayanti; Yulia Pratiwi; Gunawan Firmansyah; Mera Putri Pratitis; Nanda Intan Permatasari (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
Dengue Hemorrhagic Fever (DHF) remains a significant public health challenge in Indonesia, with the increasing prevalence of cases every year. One of the key methods of controlling the spread of DHF is to target the vector, Aedes aegypti mosquitoes, by eradicating their larvae. However, the widespread and continuous use of chemical larvicides has raised concerns regarding the development of mosquito resistance and environmental pollution. This community service activity aimed to provide students at Duta Karya Vocational High School with knowledge and practical skills to use natural, eco-friendly alternatives for controlling mosquito larvae, focusing on papaya seeds (Carica papaya) and alum as natural larvicides. The methods for this activity included interactive counseling, a demonstration on how to produce larvicides using papaya seeds and alum, and an engaging question-and-answer session. Thirty 12th-grade students from the Pharmacy class participated in this activity. The results revealed that the activity was highly effective in increasing the students' understanding and practical ability to independently create and apply natural larvicides. The students expressed a high level of enthusiasm and interest in the topic, actively participating in the discussions and demonstrations. As a result of this community service, the school has expressed interest in incorporating this activity into its School Health Unit (UKS) work program, which will further promote the use of natural, sustainable methods for controlling mosquito populations. The students, now equipped with the necessary skills, are ready to become "jumantik" cadres—community health volunteers responsible for monitoring and preventing mosquito larvae development. This initiative also raised awareness about utilizing organic waste, such as papaya seeds, to create valuable products for the prevention of DHF.